دراسة واقع نظام الإدارة البيئية في الشركة العامة لمصفاة بانياس - زاهر بسام (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هدف البحث إلى التعرف على واقع نظام الإدارة البيئية في الشركة محل البحث، والتعرف على متطلباته ومزاياه، وخطوات تطبيقه. وقد أشارت نتائج البحث إلى الآتي: - انخفاض درجة التزام الشركة محل الدراسة بوضع الاستراتيجيات والخطط والبرامج والسياسات الخاصة بالإدارة البيئية. - عدم فعالية الجهود التخطيطية والإجراءات المطلوبة للتوافق مع متطلبات نظام الإدارة البيئية. - عدم توافر أهداف استراتيجية بيئية تتوافر فيها مواصفات الأهداف الجيدة. - انخفاض درجة توافر المهارات المتخصصة والتكنولوجيا والموارد المالية لتطبيق ومراقبة نظام الإدارة البيئية. - انخفاض درجة التزام الشركة محل الدراسة بتنفيذ الاستراتيجيات والخطط والبرامج والسياسات الخاصة بالإدارة البيئية. وقد أشارت توصيات البحث إلى ضرورة قيام الشركة محل البحث بالاهتمام بالتخطيط الاستراتيجي البيئي، والقيام بإجراء مقارنة مرجعية، وتحسين الواقع البيئي للشركة محل الدراسة من خلال تطبيق دورة PDCA (التخطيط، التنفيذ، التقييم بناءً على المعايير، التحسين بناءً على نتائج التقييم)، والسعي للحصول على شهادة الأيزو 14001. The research aims at identifying the situation of environmental management system, and to identify the requirements and benefits, and steps to apply it. The research reveals the following results regarding the surveyed company: - The decrease of degree of commitment of surveyed company to put the strategies, plans, programs and policies according to environmental management. - The ineffectiveness of planning efforts, and the actions required to comply with the requirements of an environmental management system. - The lack of the objectives of an environmental strategy which meets the good goals specifications, - The decline in the availability of specialized skills, technology and financial resources to implement and monitor environmental management system - The decrease of degree of commitment of surveyed company to implant the strategies, plans, programs and policies according to environmental management. The recommendations of this research have stressed the need to be interested in the environmental strategic planning, and to do the Benchmarking, and to improve the environmental reality of the company under study through implementing PDCA cycle (plan, do, check, act), and seeking to obtain the ISO 14001 certificate.